2010
DOI: 10.1007/s11146-009-9229-4
|View full text |Cite
|
Sign up to set email alerts
|

Property Segment and REIT Capital Structure

Abstract: Property segment, REIT competition, Capital structure, G32,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Discussions of capital structure in corporate finance literature tend to begin with an analysis of trade-off theory with respect to the marginal debt tax shield versus marginal bankruptcy costs. In our case, however, the tax benefit argument is not particularly relevant since real estate entities in the UK are statutorily exempt from paying income tax as long as a minimum of 90% of their taxable income is distributed to shareholders in the form of dividends (FENG et al 2007;ERTUGRUL, GIAMBONA 2011). More specifically, if a UK REIT distributes 90% of its taxable income to shareholders using a Property Income Distribution (PID) each accounting period, no corporate income tax is owed.…”
Section: Capital Structure Theories and Real Estate Sectorsmentioning
confidence: 99%
“…Discussions of capital structure in corporate finance literature tend to begin with an analysis of trade-off theory with respect to the marginal debt tax shield versus marginal bankruptcy costs. In our case, however, the tax benefit argument is not particularly relevant since real estate entities in the UK are statutorily exempt from paying income tax as long as a minimum of 90% of their taxable income is distributed to shareholders in the form of dividends (FENG et al 2007;ERTUGRUL, GIAMBONA 2011). More specifically, if a UK REIT distributes 90% of its taxable income to shareholders using a Property Income Distribution (PID) each accounting period, no corporate income tax is owed.…”
Section: Capital Structure Theories and Real Estate Sectorsmentioning
confidence: 99%
“…Previous studies in developed countries demonstrate opposing theories in explaining debt financing behavior in the REIT industry. For instance, some studies concluded that REITs financing decisions follow the pecking order theory (Feng, Ghosh & Sirmans 2007;Morri & Beretta 2008), while Morri and Cristanziani (2009) found that REITs financing decision fully support the trade-off theory, and Ertugrul and Giambona (2010) showed partial support for pecking order theory and trade-off theory. Clark (2010) argued that many previous studies and theoretical models, such as the pecking order and trade-off models, have not been able to explain the companies' funding decisions in practice, because they overlooked the value of financial flexibility which creates an opportunity to enhance their performances (Arslan-Ayaydin et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There is a large literature that examines how REIT financing choices are influenced by their characteristics (Casey, Sumner and James , Morri and Beretta , Ertugrul and Giambona , Harrison, Panasian and Seiler ). There is also evidence that having a strong banking relationship influences capital structure choices as well as the ability of REITs to deal with financial downturns.…”
mentioning
confidence: 99%